Proliferating CLL cells express high levels of CXCR4 and CD5 - Daniel Friedman; Drshika P. Mehtani; Jennifer B. Vidler; Piers E. M. Patten; Robbert Hoogeboom (HemaSphere)
Abstract Chronic lymphocytic leukemia (CLL) is an incurable progressive malignancy of CD5+ B cells with a birth rate between 0.1% and 1% of the entire clone per day. However, the phenotype and functional characteristics of proliferating CLL cells remain incompletely understood. Here, we stained peripheral blood CLL cells for ki67 and DNA content and found that CLL cells in G1‐phase have a CXCR4loCD5hi phenotype, while CLL cells in S/G2/M‐phase express high levels of both CXCR4 and CD5. Induction of proliferation in vitro using CD40L stimulation results in high ki67 levels in CXCR4loCD5hi cells with CXCR4 expression increasing as CLL cells progress through S and G2/M‐phases, while CXCR4hiCD5lo CLL cells remained quiescent. Dye dilution experiments revealed an accumulation of Ki67hi‐divided cells in the CXCR4hiCD5hi fraction. In Eµ‐TCL1 transgenic mice, the CXCR4hiCD5hi fraction expressed high levels of ki67 and was expanded in enlarged spleens of diseased animals. Human peripheral blood CXCR4hiCD5hi CLL cells express increased levels of IgM and the chemokine receptors CCR7 and CXCR5 and migrate efficiently toward CCL21. We found higher levels of CXCR4 in patients with progressive disease and the CXCR4hiCD5hi fraction was expanded upon clinical relapse. Thus, this study defines the phenotype and functional characteristics of dividing CLL cells identifying a novel subclonal population that underlies CLL pathogenesis and may drive clinical outcomes.